ASPECTS IN AESTHETIC PREVIEW IN FIXED PROSTHODONTIC REHABILITATION RESULTS - Ana Maria Cristina Ţâncu; Mihaela Pantea; Paula Perlea; Anca Nicoleta Temelcea; Ştefan Cristian Popa; Marina Imre (Amaltea Medical Publishing House, 2018)
The aesthetic requirements and expectations of patients have increased greatly in the current social context, which has attracted increasing challenges in the clinical work of prosthodontic specialists. Thus, the predictability of the results of most types of prosthodontic restorations has become absolutely necessary to meet patients' demands, and digital aesthetic prefiguration is a useful and necessary tool. In this context, the paper presents the case of a 55-year-old patient, partially edentulous in the maxillary, rehabilitated by a 13-year-old metal-ceramic bridge. The patient was referred for the reconstruction of the maxillary bridge, which was no longer responding to the aesthetic demands. After a thorough clinical examination, the treatment plan was established and the old bridge was replaced by classical technique. The result was accepted by the patient, who appreciated it as excellent, aesthetically and functionally. To determine to what extent a digital application can bring an aesthetic value to classical coronary restoration techniques, we have used one of the newest and most advanced techniques of digital aesthetic prefiguration, the Visagism application, which has proposed an ideal look of the teeth, also taking into account the patient's temperament, the result of the computer simulation being discussed with the patient.